Pulmonary Fibrosis in COVID-19 Survivors: Predictive Factors and Risk Reduction Strategies. (11th August 2020) - Ojo, Ademola S.; Balogun, Simon A.; Williams, Oyeronke T.; Ojo, Olusegun S.
Abstract : Although pulmonary fibrosis can occur in the absence of a clear-cut inciting agent, and without a clinically clear initial acute inflammatory phase, it is more commonly associated with severe lung injury. This may be due to respiratory infections, chronic granulomatous diseases, medications, and connective tissue disorders. Pulmonary fibrosis is associated with permanent pulmonary architectural distortion and irreversible lung dysfunction. Available clinical, radiographic, and autopsy data has indicated that pulmonary fibrosis is central to severe acute respiratory distress syndrome (SARS) and MERS pathology, and current evidence suggests that pulmonary fibrosis could also complicate infection by SARS-CoV-2. The aim of this review is to explore the current literature on the pathogenesis of lung injury in COVID-19 infection. We evaluate the evidence in support of the putative risk factors for the development of lung fibrosis in the disease and propose risk mitigation strategies. We conclude that, from the available literature, the predictors of pulmonary fibrosis in COVID-19 infection are advanced age, illness severity, length of ICU stay and mechanical ventilation, smoking and chronic alcoholism. With no proven effective targeted therapy against pulmonary fibrosis, risk reduction measures should be directed at limiting the severity of the disease and protecting the lungs from other incidental injuries.